BEYOND THE BLUE ECONOMY creative industries and the fourth industrial revolution in small... island developing states. - Rudge, Peter ([S.l.] : ROUTLEDGE, 2021)
This book argues for a broader approach to sustainable growth in Small Island Developing States (SIDS). Small island states such as those in the Caribbean, Indian Ocean and South Pacific face significant and growing threats from climate change, increasing political and social volatility, and rapidly evolving global trends in technology and tourism. Based on ten years of research, this book looks beyond the Blue Economy of tourism and fisheries and provides a model of how creative industries, innovation networks, creative clusters and digital transformation can give SIDS the foundation for a strong sustainable future. The book provides not only insights into how these emerging digital-creative sectors can drive developing economies but also actionable tools for policy makers, entrepreneurs and academics to deliver increased performance on the United Nations Sustainable Development Goals and, ultimately, growth and sustainability. This book will be of great interest to scholars and practitioners of economic geography, sustainable development, development studies and the creative industries.
OCLC-licensed vendor bibliographic record.
Keywords: Marine resources development; Marine resources -- Economic aspects; Coastal zone management; Sustainable development; Economics; Finance; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Development / Economic Development